Finite Element Analysis of Interface Pressure of Transtibial Residual Limb Using Conventional and 3D-Printed Prosthetic Socket During Gait Cycle - Hairul Bakri; Adila Fazliana Che Manan; Masjuri Musa; Mohd Nazim Abdul Rahman; Nguyen Ho Quang; Guo Dong Lim; Mohd Juzaila Abd Latif (International Journal of Integrated Engineering, 2026)
This study examines the interface pressure distribution within transtibial prosthetic sockets during the gait cycle using finite element analysis (FEA) to improve comfort and load transfer for amputees. Discomfort caused by improper pressure distribution remains a major concern in prosthetic design, often leading to skin irritation, pain, and reduced mobility. To address this issue, the study compares conventional sockets with 3D-printed designs that offer enhanced customization and pressure relief. A validated FE model was developed to simulate the biomechanical interaction between the residual limb and prosthetic socket, incorporating anatomically relevant geometry and material properties. Interface pressures were analyzed at key points of interest, including the patella tendon, distal tibia end, fibula head, and popliteal regions, throughout the various phases of the gait cycle to capture dynamic pressure variations. Results indicate that 3D-printed sockets consistently demonstrate lower and more evenly distributed interface pressures than conventional sockets, with a maximum pressure reduction of 51.7% at the tibial end. The pressure values remained within established physiological limits throughout the gait cycle. The influence of knee flexion moments on pressure distribution was found to be minimal, suggesting that body weight and socket alignment are more critical factors. These findings support the application of 3D-printing technologies in prosthetic socket design to improve comfort, fit, and functionality for transtibial amputees.